Corporate Hedging and Its Effect on Firm Value - Viirimäki, Jaakko (My University, 2026)
This thesis studies the relationship between corporate hedging and firm value. Particularly, it investigates whether derivative instruments used for hedging can create additional value for a firm. Furthermore, the purpose is also to find out whether certain derivative instruments perform better at creating additional value than others. Corporate hedging is a frequently covered topic in modern financial literature, and it has received plenty of attention, especially over the past few decades. Nowadays, hedging strategies are increasingly used to manage financial risk. According to classic financial theory, hedging can create additional value by stabilizing cash flows, reducing financial distress costs, and lowering the probability of underinvestment problems. Despite the substantial amount of academic attention, empirical evidence regarding the value-enhancing effects of corporate hedging remains mixed. Therefore, this ongoing debate is the primary motivation for this study. The thesis analyzes the performance of corporate hedging as a value-enhancing strategy based on a literature review of empirical research.

Tämä opinnäytetyö tutkii yrityksen suojautumisen ja yritysarvon välistä suhdetta. Erityisesti se pyrkii selvittämään, voivatko suojautumiseen käytetyt johdannaisinstrumentit luoda yritykselle lisäarvoa. Lisäksi tarkoituksena on selvittää, toimivatko tietyt johdannaisinstrumentit muita paremmin lisäarvon tuottamisessa. Yrityksen suojautuminen on nykyisessä rahoituskirjallisuudessa usein käsitelty aihe, ja se on herättänyt paljon huomiota etenkin viime vuosikymmenten aikana. Nykyään suojautumisstrategioita käytetään yhä enemmän taloudellisten riskien hallintaan. Rahoitusteorian mukaan suojautuminen voi luoda lisäarvoa vakauttamalla kassavirtoja, vähentämällä taloudellisen häiriöiden kustannuksia ja pienentämällä sijoittamisongelmien todennäköisyyttä. Huomattavasta akateemisesta huomiosta huolimatta empiiriset todisteet yrityksen suojautumisen arvoa lisäävistä vaikutuksista ovat ristiriitaisia ja tämä debatti onkin tämän tutkimuksen ensisijainen motivaation lähde. Opinnäytetyö analysoi yrityksen suojautumisen suorituskykyä arvoa lisäävänä strategiana empiirisen tutkimuksen kirjallisuuskatsauksen pohjalta.
Keywords: finance; risk management; risks; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Kauppatieteiden kandidaattiohjelma|en=Bachelor Programme in Business Studies|; Rahoitus